Sistem Informasi Masjid Imam Malik Koppe Menggunakan Fasilitas Platform Emasjid - Muhtar Muhtar; Eka Fitrisam; Reski Idrus; Basri Basri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This research aims to develop an information system for the Imam Malik Koppe Mosque in Darma Village, Polewali District, Polewali Mandar Regency, utilizing the eMasjid platform as a solution for digitally managing mosque activities. The problem faced was the suboptimal recording of activity data, financial data, and service information for the congregation. The system development method used the Waterfall model, which consists of needs analysis, system design, implementation, testing, and maintenance. The result of this research is a mosque information system capable of presenting information on activities, financial data, reports, and communication between administrators more efficiently, transparently, and accountably. This system is expected to be an effective and user-friendly means of digitizing mosque management.